1984
DOI: 10.1111/j.1440-1827.1984.tb02188.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Polysplenia Only With Absence of the Hepatic Segment of Inferiorvena Cava in a Middle‐aged

Abstract: An autopsy case of polysplenia with absence of the hepatic segment of the inferior vena cava in a 53‐year‐old female is reported. The venous blood from the lower parts of the body was drained through the azygos vein and the superior vena cava into the right atrium. Other than acquired pathological change, the heart was found to be normal. Except for the partial absence of the inferior vena cava, isomerism of asymmetric organs, and heterotaxia of abdominal organs, characteristic of typical polysplenia, were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…When the incisures fail to fuse, they create two or more spleens [8] . The blood flow of an embryo makes a transition from symmetric to asymmetric around the 25th d to determine the visceral sidedness, and it has been suggested that this is when cono-truncal anomalies and anomalies of atrioventricular canal occur [9] . At the same time, PDPV also develop.…”
Section: Discussionmentioning
confidence: 99%
“…When the incisures fail to fuse, they create two or more spleens [8] . The blood flow of an embryo makes a transition from symmetric to asymmetric around the 25th d to determine the visceral sidedness, and it has been suggested that this is when cono-truncal anomalies and anomalies of atrioventricular canal occur [9] . At the same time, PDPV also develop.…”
Section: Discussionmentioning
confidence: 99%
“…This determines the visceral sidedness. Anomalies of conotruncus and the atrioventricular canal occur at this time (19).…”
Section: Ivc Interruption With Azygos or Hemiazygos Continuationmentioning
confidence: 99%